The Influence of Brand Image and Trust Brand Againts Xiaomi Brand Loyalty Throught Customer Satisfaction - Adam Apriansyah; Andi Hidayat Muhmin (International Journal of Asian Business and Management, 2023)
At this time smartphones are a necessity of life every day. So, every individual must have at least one smartphone as a tool for daily life. Currently, smartphone users in Indonesia are experiencing rapid development, but with so many smartphone users giving customers a variety of choices in purchasing smartphones. Various brands and specifications offered by manufacturers make the purchase and use of smartphones higher every year. With intense competition in the smartphone industry requires Xiaomi to have a strategy in order to remain in demand by consumers. This research was carried out to find out the influence of brand image, brand trust and consumer satisfaction on brand loyalty to Xiaomi smartphone consumers who live in the Tangerang area. Based on the results of this study shows that brand image has a positive effect on consumer satisfaction. Brand trust has a positive effect on consumer satisfaction. Brand image positively affects brand loyalty. Brand trust positively affects brand loyalty. Consumer satisfaction has a positive effect on consumer loyalty. Brand image positively affects brand loyalty through consumer satisfaction. Brand trust positively affects brand loyalty through consumer satisfaction